Caracteristicas de la produccion de yuca en el mundo con enfasis en America Latina - Díaz Duque, R.O. (International Center for Tropical Agriculture, 1980)
The importance of cassava cultivation in relation to other agricultural products of cassava-producing countries is briefly analyzed. The production, area and yields of cassava cultivation in all the production zones, and especially L.A. countries, were studied with the purpose of evaluating the impact on product prices and producers' income. Since the increase in production is mainly due to the increase in area sown, real prices have been almost constant throughout the period (1955-74) and the majority of the cassava produced is directly used for human consumption, one could think that both the supply on behalf of the growers and the demand for human consumption has increased in relation to the population growth. An increase in cassava production greater than 3 percent yearly would cause a lowering in prices and a reduction in the gross profit of the producer and therefore, a lack of incentives for production for the following yr. A practical solution should reduce cassava prices to levels competitive with those of other products, principally flours and starches; utilize cassava as an energetic supplement in animal concentrates or as a substrate in unicellular protein production. Export markets for starches should be studied thoroughly since sub-products from this process are of great utility in animal concentrate industries. (CIAT)